If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7p + p = -4 Combine like terms: -7p + p = -6p -6p = -4 Solving -6p = -4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '-6'. p = 0.6666666667 Simplifying p = 0.6666666667
| 2e^2+12e-22= | | -5u+2+5u= | | W+2w+w+w= | | 4x^3-16x+2=0 | | t-2.89=915 | | -8x+2(x+2)=-26 | | -11+-5= | | 7n+5-5n-6= | | -3(2x-10)=-30 | | 4x-5y=-45 | | 4x=2y+10 | | -3n+10+n+9= | | 8x-7y=-63 | | 19=6d+1 | | 3r^27=0 | | 6g+24=72 | | 6x+5-1= | | 81xy-16x=36xy | | 10v-8+5v-6= | | 9x+40+4y+8=180 | | 19p+14=89-6p | | 7+3(-8x-4)=11 | | (x+15)+(x+5)+40=180 | | -5+5t=-20 | | 10k+9+k-6= | | 10+6y-6-4y= | | 12y-8y-12=71.80 | | q+q-q=5 | | Y=2x^3-3 | | 4x-2(x-5)=-9+5x+1 | | 4k-3=3k+7 | | (3x+20)=45 |